As Práticas Turísticas na Orla Oeste da Ilha de Mosqueiro, Região Metropolitana de Belém, PA - Ribeiro, Willame de Oliveira; Costa, Maria Augusta Freitas; Tavares, Maria Goretti da Costa (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> A Ilha do Mosqueiro pertence ao município de Belém, mas localiza-se a 77 km da sua sede. A Ilha teve seu processo de valorização para o Turismo iniciado no período áureo da economia da borracha e se acelerou com a implantação da ponte ligando-a ao continente, durante a década de 1970. Este artigo objetiva apresentar as práticas turísticas na orla oeste da Ilha de Mosqueiro, identificando o processo de des-re-territorialização de tais práticas e o viés do [eco] turismo como uma possibilidade de nova significação ao uso da orla oeste da ilha. Tourist Practices in Waterfront West Island Mosqueiro, metropolitan region of Belém, PA, Brazil - The island Mosqueiro belonging to the municipality of Belem and it is located 77 km from the capital. The process for introduction of tourism practice started in the heyday of the rubber economy and it was accelerated during the 1970s with the build of the bridge connecting the island to the mainland. This article presents the tourism practices on the west of the Ilha do Mosqueiro, identifying the its process of de-re- territorialization and the [eco] tourism as a possibility for new meaning to the use of the western edge of the island. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->